STRATEGI EFEKTIF PENGELOLAAN DAN ANALISIS DATA PT. NUSANTARA BUILDING INDUSTRIES DENGAN MICROSOFT EXCEL - Diana, Arista Fitri; Sulthan Madani, Muhammad (Fakultas Teknologi Informasi dan Industri Unisbank, 2024)
Microsoft Excel is the software used to create, edit, and manage spreadsheets containing numerical and text data. Microsoft Excel allows users to perform a wide variety of tasks, such as analysis data, graphing, complex calculations, and more. This activity aims to improve the skills and understanding of PT Nusantara Building Industries (NBI) employees in using Microsoft Excel. This Microsoft Excel training focuses on the functions used for data analysis, with the formulas used in the form of logical functions. This training is designed to introduce the IF and NESTED IF logic functions. This logic function is widely used in companies, for example in financial analysis, inventory management, Human Resource Development, sales, and marketing analysis, project management, and business decisions. Through case studies and interactive excercises, participants can identify the problems given and solve them using the logical formula that has been presented. This strategy is intended to increase work effectiveness and efficiency. The evaluation result showed a good level of acceptance from participants regarding the suitability and benefits of the material presented. This community service activity succeeded in having a positive impact in increasing the competence in employees of NBI companies utilizing Microsoft Excel technology.